Reduced UVB-induced corneal damage caused by reactive oxygen and nitrogen species and decreased changes in corneal optics after trehalose treatment - Cejková, Jitka; Cejka, Cestmír; Ardan, Taras; Sirc, Jakub; Michálek, Jirí; Luyckx, Jacques (Histology and histopathology, 2010)
Trehalose, a nonreducing disaccharide of glucose, produced and stored in many lower and higher organisms, although not in mammals, is synthetized as a stress responsive factor when cells are exposed to various environmental stress conditions. Recently, trehalose has been implicated in various situations in mammals. The aim of this paper was to examine whether trehalose might decrease the damage of the rabbit cornea evoked by UVB rays. During irradiation with UVB rays, consisiting of a daily dose of 0.5 J/cm2 for four days, trehalose was applied in eye drops on the right eye and buffered saline on the left eye. One day after the end of irradiation the animals were sacrificed and the corneas examined spectrophotometrically for light absorption. Another group of corneas similarly treated were examined morphologically and immunohistochemically. Corneal thickness (hydration) was measured using a Pachymeter. The results show that compared to buffered saline, trehalose treated corneas displayed fewer corneal disturbances during UVB irradiation. The increases in corneal hydration and light absorption were less pronounced and intracorneal inflammation and corneal neovascularization were suppressed. Nitric oxide synthases that generate nitric oxide were less expressed in the cornea, and formation of cytotoxic peroxynitrite (demonstrated by nitrotyrosine residues) was decreased. The expression of the antioxidant aldehyde dehydrogenase3A1 was less inhibited in the corneal epithelium, and apoptotic corneal epithelial cell death (detected by immunostaining for active caspase-3) was greatly diminished. In conclusion, trehalose reduced UVB-induced damage caused by reactive oxygen and nitrogen species and decreased changes in the corneal optics.
Keywords: oxidační stres; trehalosa; rohovka; reaktivní formy kyslíku; reaktivní formy dusíku; imunohistochemie; Corneal Injuries; Trehalose; Ophthalmic Solutions; králíci; ultrafialové záření; Reactive Oxygen Species; Animals; oční roztoky; Immunohistochemistry; zvířata; Reactive Nitrogen Species; Rabbits; Ultraviolet Rays; apoptóza; spektrofotometrie; poranění rohovky; Spectrophotometry; Oxidative Stress; Cornea; Apoptosis